LRRC25 expression during physiological aging and in mouse models of Alzheimer’s disease and iPSC-derived neurons - Devadoss, Dinesh; Akkaoui, Juliet; Nair, Madhavan; Lakshmana, Madepalli K. (Frontiers in Molecular Neuroscience, 2024)
The leucine-rich repeat-containing protein 25 (LRRC25) is relatively a novel protein with no information on its role in neuronal or brain function. A recent study suggested LRRC25 is a potential risk factor for Alzheimer's disease (AD). As a first step to understanding LRRC25's role in the brain and AD, we found LRRC25 is expressed in both cell membranes and cytoplasm in a punctuate appearance in astrocytes, microglia, and neurons in cell lines as well as mouse brain. We also found that LRRC25 expression is both age-and brain region-dependent and that 1-day-old (1D) pups expressed the least amount of LRRC25 protein compared to adult ages. In the APΔE9 mice, immunoblot quantified LRRC25 protein levels were increased by 166% (**, p<0.01) in the cortex (CX) and by 215% (***, p<0.001) in the hippocampus (HP) relative to wild-type (WT) controls. Both the brainstem (BS) and cerebellum (CB) showed no significant alterations. In the 3xTg mice, only CX showed an increase of LRRC25 protein by 91% (*, p<0.05) when compared to WT controls although the increased trend was noted in the other brain regions. In the AD patient brains also LRRC25 protein levels were increased by 153% (p<0.001) when compared to normal control (NC) subjects. Finally, LRRC25 expression in the iPSC-derived neurons quantified by immunofluorescence was increased by 181% (**, p<0.01) in AD-derived neurons when compared to NC-derived neurons. Thus increased LRRC25 protein in multiple models of AD suggests that LRRC25 may play a pathogenic role in either Aβ or tau pathology in AD. The mechanism for the increased levels of LRRC25 in AD is unknown at present, but a previous study showed that LRRC25 levels also increase during neonatal hypoxic-ischemia neuronal damage. BBased on the evidence that autophagy is highly dysregulated in AD, the increased LRRC25 levels may be due to decreased autophagic degradation of LRRC25. Increased LRRC25 in turn may regulate the stability or activity of key enzymes involved in either Aβ or hyperphosphorylated tau generation and thus may contribute to increased plaques and neurofibrillary tangles.